1984
DOI: 10.1097/01241398-198403000-00108
|View full text |Cite
|
Sign up to set email alerts
|

Interviews With Parents of Boys Suffering From Duchenne Muscular Dystrophy

Abstract: Results Problems experienced by parentsEarly in the interview, parents were asked what problems they had experienced in caring for their affected sons. A total of 11 3 problems were reported, but since some w rd W W d v, N m m 0'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 3 publications
1
18
0
1
Order By: Relevance
“…Firth et al have pointed out that many parents were frustrated and often bitter over the long delays experienced in obtaining the diagnosis of muscular dystrophy in their children (Firth, Gardner-Medwin, Hasking & Wilkinson, 1983). The age range of diagnosis in this study was 5-9 yr, and the duration between onset of earliest identified symptoms and the diagnosis ranged between 2 and 5 yr.…”
Section: Discussionmentioning
confidence: 95%
“…Firth et al have pointed out that many parents were frustrated and often bitter over the long delays experienced in obtaining the diagnosis of muscular dystrophy in their children (Firth, Gardner-Medwin, Hasking & Wilkinson, 1983). The age range of diagnosis in this study was 5-9 yr, and the duration between onset of earliest identified symptoms and the diagnosis ranged between 2 and 5 yr.…”
Section: Discussionmentioning
confidence: 95%
“…Finally they experienced emotional problems with depression, social isolation, negative attitudes, and diminished expectation of their sons' potential. [7][8][9] This study was designed to evaluate the parental perceptions of the importance of services, health issues, and aspects of quality of life in boys with Duchenne muscular dystrophy. We also explored changes in importance as the disease progressed in order to help identify the evolution of required services.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, caregivers grieved their loved one's progressive loss of function, feared for the future, and worried about the genetic status of subsequent generations (Bostrom et al, 2006;Gravelle, 1997;Mah et al, 2008). Parents of children with neuromuscular disease reported feeling guilty that they gave their nonaffected children less attention and that these children often became responsible for a portion of the caregiving (Firth, Gardner-Medwin, Hosking & Wilkinson, 1983). This is similar to findings by Mah et al (2008), who found that the priorities of other family members come second to those of the child with neuromuscular disease.…”
Section: Caregivingmentioning
confidence: 95%
“…In particular, individuals with MND stressed the importance of social support, namely, their family and caregivers (Fanos, Gelinas, Foster, Postone, & Miller, 2008;Hugel et al, 2006). Isolation, suffering, sorrow, and guilt were recurrent themes throughout the neuromuscular caregiving literature (Bostrom, Ahlstrom, & Sunvisson, 2006;Firth, Gardner-Medwin, Hosking, & Wilkinson, 1983;Gravelle, 1997). In particular, caregivers grieved their loved one's progressive loss of function, feared for the future, and worried about the genetic status of subsequent generations (Bostrom et al, 2006;Gravelle, 1997;Mah et al, 2008).…”
Section: Caregivingmentioning
confidence: 97%